Exploring Genetic Variations: Polyploid Mutants in Grape Cultivation - Guliyev, V.M. (Current Research Progress in Agricultural Sciences Vol. 8, 2025)
In order to produce experimental polyploid forms, almost all the methods used are based on the influence of mutagenic agents on actively dividing somatic cells in the selection of grapes. As a result, the obtained genomic mutations are mitotic autotetraploids according to genetic properties. Under the influence of natural mutagenic factors, spontaneous mitotic polyploids usually occur in grapes as a result of the non-disjunction of chromosomes in anaphase. These days, the selection of grapes to obtain new initial polyploidy material with various inductions of mitotic genomic mutations with the help of colchicine and other mutagens. The duration and complexity of the selection process called for a new method that would increase efficiency and accelerate the selection of polyploid forms of grapes. The study describes the impact of various concentrations of colchicine aqueous solution during inflorescence at the meiosis stage of 3 grape cultivars. A new method for preparing a genomic mutation in the meiotic stage of gametogenesis in the grapes under the influence of colchicine was developed and it is described briefly. The study revealed that mutational efficiency constitutes 2.2-28.0%. This new technique allows for the induction of genomic mutations at the meiosis stage in grapes. The cyto-anatomical and histological analysis of polyploid mutant forms of grapes revealed cytogenetic and histological mutational variation. Genetic analysis of variability is given.